Feather hydrolysate as a promising nitrogenârich fertilizer for greenhouse lettuce cultivation - Lisiane Sobucki; Rodrigo Ferraz Ramos; Elci Gubiani; Gustavo Brunetto; Douglas Rodrigo Kaiser; Daniel Joner Daroit (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Poultry agro-industry generates huge amounts of solid wastes, such as poultry litter (PL) and feathers. Feathers, possessing a substantial amount of organic nitrogen, are mainly converted into feather meal (FM) through the hydrothermal process; however, microbial conversion into feather hydrolysates (FH) is increasingly being focused on. Since waste management strategies include the use of organic wastes as soil fertilizer, PL, FM, and FH were evaluated as fertilizers for lettuce in comparison to urea. Methods Lettuce seedlings were transplanted to soil pots containing FH, obtained through feathersâ bioconversion by Bacillus sp. CL18, FM, PL, urea, and unfertilized controls. Partial chemical characterization of FH, FP, and PL was performed. Fertilization treatments were applied to reach 180 kg N/ha. Growth, dry biomass, and chlorophyll contents of lettuce were evaluated to indicate fertilizer performance. Results After 60 days of greenhouse lettuce cultivation, leaves per plant were superior after FH treatment. Lettuce fertilized with urea and FH presented higher and similar foliar areas. FH treatment resulted in increased dry weight (DW) of leaves, which then decreased in the order urea>FM>MM~controls>PL. Dry weight of leaves and roots was 33% and 64% higher with FH than with urea. Leaf total chlorophyll content was higher with FH, but similar to urea and FM. Lettuce growth was negatively affected by PL when compared to controls. Conclusion FH, obtained from microbial processing of abundant and inexpensive feathers, could be a candidate N-rich fertilizer for lettuce cultivation.